Natal and Neonatal Teeth: A Retrospective Study of 15 Cases - Basavanthappa, Nagaveni N; Kagathur, Umashankara; Basavanthappa, Radhika N; Suryaprakash, Satisha T (European Journal of Dentistry, 2011)
Objectives: To present 17 natal/neonatal teeth in 15 patients and describe their clinical characteristics, associated disorders, complications and treatment. Methods: A retrospective study of neonates who visited the Department of Pedodontics and Preventive Dentistry, College of Dental Sciences, Davangere, India, between 2003 and 2006 was carried out. It was a study of clinical data, such as the age and gender of the patients, the history and chief complaints of mothers, the clinical appearance and location of natal/neonatal teeth, and associated complications and treatments. Results: A total of 17 teeth (6 natal, 11 neonatal) were found in 15 patients. No significant gender predilection (8 male, 7 female) was found. Sixteen natal/neonatal teeth were placed in mandibular incisor area (10 on the right side and 6 on the left side) and one tooth in the maxillary incisor area. In 13 patients, the occurrence of natal/neonatal teeth was unilateral, and in 2 patients, it was bilateral. Three cases were associated with enamel hypoplasia, 3 cases with Riga-Fede disease, and 1 case with gingival hyperplasia. One case involved a patient with cleft lip and palate. Radiographic examination confirmed these teeth to be supernumerary, and all teeth exhibited hypermobility. Extraction had been done in all the cases. Eleven of the extracted teeth exhibited only rudimentary roots, and six teeth showed no roots. Conclusions: The occurrence of a natal/neonatal tooth is a rare phenomenon. When it occurs, the teeth have a variety of clinical characteristics and lead to different complications. Knowledge of the management of these structures is essential for the overall well being of a child. (Eur J Dent 2011;5:168-172)
Keywords: Natal tooth; Neonatal tooth; Vitamin K; Riga-Fede disease; Gingival hyperplasia; Cleftlip and palate